Mechanical behavior of isolated intervertebral disc - Lemos, F. F. [UNESP]; Tomazini, J. E. [UNESP]; Oliveira, U. G. [UNESP] (My University, 2009)
The study on several components of intervertebral joints is essential to understand the spine's degenerative mechanisms and to assess the best method for their treatment. For such study it is necessary to know the mechanical properties of the isolated intervertebral disc (ID) mechanical properties and, it is necessary to evaluate its stresses and strains. In order to assess the ID displacements, a fine, U-shaped blade was developed, over which two extensometers connected in a Wheatstone bridge were placed. The device was then tested on porcine spine ID, where compression loads were applied and the extremities displacements of the blade coupled to the intervertebral disc were measured. Stress/strain diagram, both on the compression and on the decompression phases, evidencing the non-linear nature of such relationship. With the experiment, it was possible to obtain approximate values of the longitudinal elasticity module (E) of the disc material and of the Poisson coefficient (n ). After several tests, E results are compatible with those obtained by others studies, with very simple and low-cost device. This experiments can be used for obtained others mechanical properties of isolated ID with precision and accuracy.
Keywords: Axial displacement; Compression; Intervertebral disc; Mechanical properties; Porcine model; Axial displacements; Compression loads; Intervertebral discs; Intervertebral joints; Low-cost devices; Mechanical behavior; Non-linear; Poisson coefficients; Porcine models; Stress/strain; U-shaped; Wheatstone bridges; Biomechanics; Biomedical engineering; Biophysics; Bridge circuits; Elasticity; Experiments; Image processing; Imaging systems; Mechanisms; Medical imaging; Stresses; Structural design